Variations in Soil Bacterial Composition and Diversity in Newly Formed Coastal Wetlands - Li, Wenbing; Lv, Xiaofei; Ruan, Junchao; Yu, Miao; Song, Yao-Bin; Yu, Junbao; Dong, Ming (Frontiers in Microbiology, 2019)
Coastal ecosystems experience some of the most active land-ocean interactions in the world, and they are characterized by high primary productivity and biological diversity in the sediment. Given the roles of microorganisms in soil biogeochemical cycling and their multifaceted influence on soil ecosystems, understanding the variations and drivers of soil microbial communities across coastal ecosystems is critical. Here, we studied soil bacterial community dynamics at different sites (from seawater to freshwater) in the Yellow River Delta, China. Bacterial community composition and diversity over four seasons were analyzed through 16S rRNA genes. Notably, the bacterial community near the ocean had the lowest alpha-diversity when compared with the other sites. No significant differences in bacterial communities among seasons were found, indicating that seasonal variation in temperature had little influence on bacterial community in the newly-formed wetlands in the Yellow River Delta. Bacterial community structure changed substantially along the salinity gradient, revealing a clear ecological replacement along the gradual transformation gradient from freshwater to seawater environment. Redundancy analysis revealed that salinity was the main driver of variations in bacterial community structure and explained 17.5% of the variability. Our study provides a better understanding of spatiotemporally-determined bacterial community dynamics in coastal ecosystems.